Comparison of Cytokine Profile between Postmenopausal Women with and Without Osteoporosis – A Case-Control Study - Soh, Geok Ting; Mohammad, Affaf Hulma; Syed Isa, Sharifah Nur Liyana; Chin, Kok-Yong; Mohamed, Norazlina (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Chronic low-grade inflammation is involved in the pathogenesis of postmenopausal osteoporosis, but the cytokines implicated remain elusive. Objective: This study aimed to compare the difference in cytokine profile between postmenopausal women with and without osteoporosis in Klang Valley, Malaysia. Methods: Postmenopausal women with (n = 20) and without osteoporosis (n = 20) were recruited for this study. Their bone health status was determined using dual-energy X-ray absorptiometry. Their fasting blood was collected for proteomic analysis. A protein array was performed for four subjects randomly selected from each group to screen the potential cytokines. Three cytokines at least 20% different between groups and consistently expressed by each subject were selected for validation using enzyme-linked immunosorbent assays (ELISA). Results: The protein array screening demonstrated that platelet-derived growth factor-BB, interleukin- 6 receptor (IL-6R), and tissue inhibitor of metallopeptidase-2 were higher in women with osteoporosis than women without osteoporosis (n = 4 per group), and consistently expressed by all women. Only body mass index (BMI)-adjusted logarithmically transformed IL-6R levels were lower among postmenopausal women with osteoporosis compared to women with normal bone health (p = 0.026) (n = 16 per group) in the ELISA test. Conclusion: IL-6R was lower among postmenopausal women with osteoporosis compared to women with normal bone health after adjusting for BMI. However, a large-scale epidemiological study with proteomic analysis needs to confirm the findings.
Keywords: inflammation